Theory of Planned Behaviour and Readiness for Changes: Implication for Organisations - Ogbodoakum, Nnamdi; Abiddin, Norhasni Zainal (Universitas Pendidikan Indonesia, 2017)
ABSTRACT: An organisationâ€™s long term survival in todayâ€™s challenging environment will depend on constant adaptation to changes in the environment. The majority of behavioural theories acknowledged individual as the central focus. Certain environmental or situational factors and applicable change-related processes have been recognised and studied as having significant influence in determining individual, group, and organisational behaviours. In the context of readiness for change, the theory of planned behaviour would be suitable in assessing the change supporting attributes of employees in achieving a strong readiness for change status. The connection between the theory of planned behaviour and individual readiness for change is that if a person has positive evaluation of change effort (attitude), supported by his close peers (subjective norm), and is confident that such change efforts will be undertaken successfully (perceived behavioural control), there will be improved motivation (intention) to actually engage in the change effort (readiness for change). This paper will discuss the Theory of Planned Behaviour and the readiness for change in organizations.KEY WORD: Readiness for Change; Attitude; Intention; Organisation; Human Resource Development.Â ABSTRAKSI: â€œTeori Tingkah-Laku Terancang dan Kesediaan untuk Berubah: Implikasi pada Organisasiâ€. Jangka hayat sesebuah organisasi dalam persekitaran yang mencabar hari ini bergantung kepada penyesuaian yang berterusan terhadap perubahan persekitaran. Kebanyakan teori tingkah-laku mengakui bahawa individu merupakan tumpuan utama dalam perubahan. Faktor persekitaran atau situasi tertentu dan proses yang berkaitan dengan perubahan juga telah diiktiraf dan dikaji sebagai mempunyai pengaruh yang besar dalam menentukan tingkah-laku individu, kumpulan, dan organisasi. Dalam konteks kesediaan untuk berubah, teori tingkah-laku terancang adalah sesuai dalam menilai perubahan sifat-sifat pekerja dalam menentukan kesediaan mereka yang kukuh untuk berubah. Hubungan antara teori tingkah-laku terancang dan kesediaan untuk berubah adalah berkaitan dengan: seseorang mempunyai penilaian positif terhadap usaha untuk berubah (sikap), disokong pula oleh rakan-rakannya yang rapat (norma subjektif), dan yakin bahawa usaha perubahan tersebut dilaksanakan dengan jayanya (kawalan tingkah-laku) dan motivasi yang ditambah baik (niat) akan benar-benar terlibat dalam usaha perubahan (kesediaan untuk berubah). Artikel ini menerangkan tentang Teori Tingkah-Laku Terancang dan kesediaan organisasi untuk berubah.KATA KUNCI: Kesediaan untuk Berubah; Sikap; Niat; Organisasi; Pembangunan Modal Insan.Â Â About the Authors: Nnamdi Ogbodoakum is a Ph.D. Student at the Department of Professional Development and Continuing Education, Faculty of Educational Studies UPM (Putra University of Malaysia) in Serdang, Selangor, Malaysia. Assoc. Prof. Dato Dr. Norhasni Zainal Abiddin is a Senior Lecturer at the Department of Professional Development and Continuing Education, Faculty of Educational Studies UPM, 43400 UPM Serdang, Selangor, Malaysia. E-mail: nonie@upm.edu.myHow to cite this article? Ogbodoakum, Nnamdi Norhasni Zainal Abiddin. (2017). â€œTheory of Planned Behaviour and Readiness for Changes: Implication for Organisationsâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.2(1) March, pp.1-18. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online).Chronicle of the article: Accepted (November 29, 2016); Revised (January 25, 2017); and Published (March 30, 2017).